Analisa Gangguan Pada Hasil Perawatan Distributor Valve Kereta - Zulkarnain, Akbar; Ramadhani, Yunus Dwi (Politeknik Perkeretaapian Indonesia Madiun, 2019)
Distributor valve is one part of the air braking system that functions as a pressure regulator between the brake cylinder, auxiliary reservoir and brake pipe on the braking system that requires maintenance. In reality in the field, there is maintenance still found disturbances in the distributor valve, so it is considered to hamper the effectiveness of maintenance. Therefore it is necessary to make research to find out what are the factors that often cause interference with distributor valve maintenance. In this study an analysis was done using a Pareto diagram to determine the percentage of interference that often occurs in the distributor valve maintenance results. After analysis, the results are 1) the pressure on the brake cylinder is more than 3.8 bar at 37.7%, 2) the release time is more than 20s time (standard 15-20s) at 26.6%, 3) the application / brake time is more than 5s (3-5s standard) at 20% and 4) leakage in the distributor valve cracks at 15.5%. From the results of research and direct observation in the field it can be seen that the factors causing interference after distributor valve maintenance on the train is the incompatibility of procedures and tools used to treat distributor valves.